2002
DOI: 10.1002/tea.10023
|View full text |Cite
|
Sign up to set email alerts
|

Development and application of a two‐tier multiple choice diagnostic instrument to assess high school students' understanding of inorganic chemistry qualitative analysis*

Abstract: This article describes the development and application of a two-tier multiple choice diagnostic instrument to assess high school students' understanding of inorganic chemistry qualitative analysis. The development of the diagnostic instrument was guided by the framework outlined by Treagust. The instrument was administered to 915 Grade 10 students (15 to 17 years old) from 11 schools after they had learned the theory involved in qualitative analysis and after a series of qualitative analysis practical sessions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(75 citation statements)
references
References 24 publications
2
68
0
5
Order By: Relevance
“…For example in chemistry, Tan et al (2002) developed a diagnostic instrument on inorganic chemistry and qualitative analysis. Similarly, Taber and Tan (2010) proposed a diagnostic two-tier questionnaire on ionization energy.…”
Section: Types and Uses Of Two-tier Itemsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example in chemistry, Tan et al (2002) developed a diagnostic instrument on inorganic chemistry and qualitative analysis. Similarly, Taber and Tan (2010) proposed a diagnostic two-tier questionnaire on ionization energy.…”
Section: Types and Uses Of Two-tier Itemsmentioning
confidence: 99%
“…Within Asian contexts, a growing body of research has explored the use of two-tier items, some entirely multiple choice and others with open-ended components (Taber and Tan 2011;Tan et al 2002;Tsui and Treagust 2009). In the current findings, the data from the LPDI, which were collected in Asian settings (i.e., Singapore and Korea) showed results consistent with the notion that tier-2 reasoning items would be harder than tier-1 knowledge items.…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…Selain itu tingkat pemahaman siswa pada tes pilihan ganda hanya dilihat berdasarkan jumlah jawaban yang benar. Beberapa peneliti [5,6,7,8,9,10] telah mengembangkan bentuk tes yang dapat digunakan untuk menentukan konsep alternatif peserta didik. Instrumen tes tersebut mampu mendeteksi miskonsepsi dan memiliki kemungkinan sangat kecil bagi siswa untuk menebak, yaitu dengan menggunakan two tier test.…”
Section: Pendahuluanunclassified
“…In order to make sense of the procedures, reactions and results in QA practical work , knowledge of topics such as acids and bases, salts, periodicity, reactivity of metals, balancing of chemical equations are important pre-requisites. Without such knowledge of required theory to guide their experiments they would not know what to take note of in the experiments (Hart, Mulhall, Berry, Loughran & Gunstone, 2000) A number of studies have found QA to be a difficult topic for secondary students, (Duit & Treagust, 1995;Gunstone, 1994;Wittrock, 1994;Nakhleh & Krajcik, 1994;Herron, 1996, Tan, Goh, Chia & Treagust, 2001, 2002 They asserted that the difficulties were due to reasons such as the content of the topic, lack of appropriate framework, the lack of cognitive strategies, cognitive overloading and the lack of mastery of process skills. Another possible reason was attributed to their teachers not having adequate understanding of the reactions and procedures involved and so are therefore unable to teach for understanding.…”
Section: Introductionmentioning
confidence: 99%